THE EFFECT OF JOB STRESS, BENEFITS, USER SATISFACTION, EDUCATION LEVEL AND TRAINING ON ACCOUNTING INFORMATION SYSTEM PERFORMANCE - Paramadewi, Putu Monique; Putra, I Nyoman Wijana Asmara (Transpublika Publisher, 2024)
The application and utilization of computer-based information systems will make it easier to face competition in the era of globalization. The way a company uses its financial information system can affect how well that system works for that business. This research aims to determine the effect of work stress, performance allowances, user satisfaction, education and training on the performance of accounting information systems. The research population is employees of the Denpasar City Regional Secretariat who use an accounting information system. A purposive sampling method was used, including a total of 60 participants. The collected data was then subjected to analysis utilizing multiple linear regression techniques. The study findings reveal that the work stress variable has a detrimental impact on the functioning of the accounting information system. The factors of allowances, user satisfaction, education level, and training are beneficial to the performance of the accounting information system. The independent variables have a major effect of 73.8% on the performance of the accounting information system, while the remaining 26.2% is attributed to other considerations.